Characterization of the polarity of cempedak wood extractive (Artocarpus integer (Thunb) Merr. Issue 1 (October 2020) - Syahidah,; Sanusi, Djamal
Abstract: Recently, timber utilization originating from community forests has become an alternative to replacing commercial timber species from natural forests. The utilization efficiency of the wood must be in accordance with their basic properties, such as the extractive content, which greatly affects the natural durability of wood. Extractive content is compounds that can be extracted using polar and non-polar solvents. Cempedak wood ( Artocarpus integer (Thunb) Merr is one type of wood from community forests, which is commonly found in South Sulawesi with various uses. The aim of this study is to analyze the polarity of extractive compounds of cempedak wood. The parameters measured in this study, namely extractive compounds, including tannin, polyphenols, and flavonoid from the n-hexane and methanol extracts. The results show that the extractive content of cempedak wood is classified as high (12.16%), the solubility of extractive content in polar solvents (methanol, 11.07%) is higher compared to the solubility in non-polar solvents (n-hexane, 1.09%). The highest levels of tannin, flavonoids, and polyphenols sequentially were found in the fraction of sapwood residue, butanol heartwood fraction and sapwood fraction. Therefore it can be concluded that the extractive content of cempedak wood is dominated by polar compounds.